Coumarin 545: an emission reference dye with a record-low temperature coefficient for ratiometric fluorescence based temperature measurements. Issue 4 (7th January 2015) - Mao, Deqi; Liu, Xiaogang; Qiao, Qinglong; Yin, Wenting; Zhao, Miao; Cole, Jacqueline M.; Cui, Jingnan; Xu, Zhaochao
Abstract : The emission intensities of coumarin 545 solution exhibit a low temperature dependence, with a record-low temperature coefficient of only ∼0.025% per °C. Abstract : The emission intensities of coumarin 545 solution exhibit a low temperature dependence, with a record-low temperature coefficient of only ∼0.025% per °C. This monomer-aggregate coupled fluorescence system can be used for ratiometric temperature measurements with high spatial and temporal resolutions; three different working modes have been demonstrated.